Practices Regarding Safe Urinary Catheterization among Healthcare Workers - Amina Aftab, Sadiq Jan, Sabeen Khan, Lala Rukh (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess the knowledge and practices regarding safe urinary catheterization among health care workers Study Design: It was a Cross sectional observational study. Methodology: Ninety two health care workers were interviewed in two hospitals from April 2022 to July 2022. A questionnaire was designed about individual and departmental practices of urinary catheterization, including the practice of hand hygiene, wearing gloves, maintaining a sterile barrier and using a non-touch gentle insertion technique and post insertion catheter care. Results: Fifty respondents were doctors, while 42 were paramedics. Hand washing and using sterile gloves were reported by 67.3% and 91.2% respectively. 71.7% cleaned the area with antiseptic but only 56.5% practiced appropriate method. 67.3% had a separate sterile catheterization tray. 68.5% respondents inserted the catheter without touching its tip. Other safety measures including arrangement of prefilled syringe for inflation of balloon (89.1%), clear visualization of urethral meatus (90%), gentle insertion (84.7%), confirmation of urine flow (86.9%), and holding the catheter in place while balloon inflation (82.6%) were variably practiced. 61.9% had mistakenly passed the catheter into vagina instead of urethra at some occasion in life. 83.6% thought it necessary to hang the urine bag on bed side for safe care, but more than 84% frequently found the urine bags on the floor in their wards. Conclusion: Safe urinary catheterization practices need to be improved. Units must develop set protocols to reduce the incidence of catheter associated morbidity. This can be achieved by continuous training and audit within the department. Keywords: urinary catheter, urinary tract infection, patient safety.